2013
DOI: 10.1111/jcpp.12159
|View full text |Cite
|
Sign up to set email alerts
|

Parent and youth report of youth anxiety: evidence for measurement invariance

Abstract: Findings provide further evidence for the importance of considering youth report when evaluating anxiety in African-American families. The SCARED was invariant across informant reports, suggesting that it is appropriate to compare mean scores for these raters and that variability in parent and youth report is not attributable to their rating different constructs or using different thresholds to determine when symptoms are present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 34 publications
6
36
1
Order By: Relevance
“…Second, we present an applied example of the importance of testing measurement invariance across informants, particularly parents and children. Our results build on the previous work of both Dirks et al (2014) and Janssens et al (2015) by explicating that conceptual similarity across informants or shared item content on forms, are not enough. Prior to comparing mean levels of any constructs, researchers should take care to ensure that the same constructs have been captured in all groups by testing the invariance of their measurements.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Second, we present an applied example of the importance of testing measurement invariance across informants, particularly parents and children. Our results build on the previous work of both Dirks et al (2014) and Janssens et al (2015) by explicating that conceptual similarity across informants or shared item content on forms, are not enough. Prior to comparing mean levels of any constructs, researchers should take care to ensure that the same constructs have been captured in all groups by testing the invariance of their measurements.…”
Section: Discussionsupporting
confidence: 65%
“…The authors identified partial measurement invariance, suggesting that measurement operation was largely equivalent across informants. Dirks et al (2014) found support for partial measurement invariance of the Screen for Child Anxiety Related Emotional Disorders across caregiver-child dyads. Their finding that the measurement of anxiety constructs was not fully equivalent across parent and child reports may be representative of a larger, unidentified issue in clinical multiple-informant assessment.…”
Section: The Case For Measurement Invariancementioning
confidence: 88%
See 1 more Smart Citation
“…If informants' reports do not come from measures for which their scores carry the same properties, then differences between reports might be parsimoniously explained by measurement error. Consequently, in recent years research on multi-informant assessment has focused on the measurement invariance of parallel forms administered to multiple informants (e.g., Dirks et al 2014), or whether scores from reports of multiple informants can be meaningfully interpreted as carrying the same or similar psychometric properties. However, only recently have these methods begun to be applied to understanding the measurement invariance of adolescents' and parents' reports of family functioning (e.g., Gross et al 2016;Janssens et al 2015).…”
Section: An Increased Focus On Measurement Invariancementioning
confidence: 99%
“…We were limited to mother-reported child anxiety at this age. Typically, mother-report of anxiety underestimates self-reported child anxiety (Dirks et al, 2014). Therefore, any bias in mother-reported anxiety in this study may be towards under-identification.…”
mentioning
confidence: 87%